A Passive Malaysian Residential Building With A Hydronic Radiator - Azhaili, Baharun; Siti, Halipah Ibrahim; Mohammad Omar, Abdullah; Ooi, Koon Beng (International journal of recent research and applied studies, 2011)
This paper presents a study to find a ‘green’ alternative to the conventional air conditioner seen on the walls of many residential buildings in Malaysia. EnergyPlus®, the official building simulation software of the US Department of Energy, is used to model a row of four units of modern low cost terrace housing, end walls facing East and West to minimize exposure to the sun’s ray. The high altitude of the tropical sun heats the metallic roofs to above 60°C during the day and the attic is naturally cooled by outdoor air infiltration through effective leakage area of 2342m2 per unit. Insulation of R-value 2.5 (m2.K)/W is added above the ceilings. Simulations are run with outdoor dry bulb temperatures that are exceeded, on average, by 0.4% (35 hours) in a year, for Kuching, in East Malaysia. Typical meteorological year data shows that the maximum nightly temperatures in Kuching are about 25°C and in West Malaysian cities with World Meteorological Organisation stations are about 26°C. When radiative heat loss to the dark night sky is included, water can be cooled to 25°C. Preliminary simulations verify that beam solar radiation enters through the windows, and external window shades lower the maximum indoor temperature in the hottest West end unit, unoccupied, by 0.6°C to 30.5°C. Night cooled water circulated to a hydronic radiator, then lowers the maximum ‘well-mixed’ operative temperature of the unit, occupied, to below 30.2°C. The indoor air is stratified to a hotter upper and a lower cooler layer, and the occupant’s environment is comfortable with air speeds of 0.8m/s.